How does import processing time impact export patterns?. (20th March 2019) - Hayakawa, Kazunobu; Laksanapanyakul, Nuttawut; Yoshimi, Taiyo
Abstract: We examine how import processing time, which is one of the major obstacles in international trade, affects export patterns at the establishment level. Investigating the effect of such time costs on export patterns reveals how smoothness or sluggishness in operations at one stage affects all stages in an international production network. We first discuss the effects of import processing time on exports, export shipment frequency and exports per shipment from a theoretical standpoint. We employ highly detailed customs data for Thailand from 2007 to 2011 to empirically investigate our theoretical predictions. Import processing time is measured using the difference between the dates on which import shipments arrive in ports and when they were released from the container yard. Results suggest that longer import processing times reduce total exports, particularly as a result of decreasing export frequency; this testifies to the importance of time costs in international trade. It is also revealed that negative effects of import processing time on exports per shipment appear in some specific instances, such as in the case of sea transportation. These results imply that the time spent in one stage has significant effects on both upstream and downstream stages in international production networks.